PERANCANGAN KARAKTER IP 3D YANG MENGADAPTASI SATWA BADAK JAWA UNTUK USIA 18-25 TAHUN - Hanif Al Ihsan; Sultan Arif Rahmadianto; Ayyub Anshari Sukmaraga (Sainsbertek Jurnal Ilmiah Sains & Teknologi, 2026)
This final project focuses on the design of a 3D character IP inspired by the Javan Rhino, one of Indonesia’s critically endangered species. The goal of this project is to raise awareness of wildlife conservation among the younger generation (ages 18–25) through an engaging and meaningful visual medium. The research methodology combines literature study, comparative analysis, and questionnaires to gather data of the target audience and their perception of fictional animal-based characters. Based on these findings, a biomechanical character named "RS-BJ62: Raksasa" was developed, embodying the archetype of "The Hero" and symbolizing protection and resilience in a dystopian future. The design process involved narrative and visual concept development, exploration of archetypes and silhouettes, 3D modeling using Blender, and documentation through a digital artbook. Various supporting media such as merchandise and promotional visuals were also designed to enhance the character’s potential as an original IP. This project seeks to combine visual creativity with real-world relevance, using character design as a tool for impactful storytelling and conservation awareness.